Subjective Experiences During Sedation Induced by Equipotent Dose of Dexmedetomidine, Propofol, Sevoflurane and S-ketamine - Koskinen, Lauri (My University, 2019)
Studies conducted in clinical and experimental settings have shown that unresponsive persons undergoing anesthetic infusion often report subjective experiences, such as dreaming, when interviewed afterwards. The aim of the present study was to investigate the presence and quality of subjective experiences in healthy young participants sedated with dexmedetomidine, propofol, sevoflurane or S-ketamine. We addressed how participant’s responsiveness (measured as behavioral response to auditory stimulus) during sedation is related to reporting experiences. Further, we explored the differences between anesthetics in the prevalence and nature of subjective experiences. Participants received equisedative doses of either dexmedetomidine (n = 40), propofol (n = 40), sevoflurane (n = 41), or S-ketamine (n = 24) and were interviewed of their subjective experiences immediately after termination of anesthetic administration. The interview transcripts were content analyzed by two independent raters for dream-likeness, incorporations of the experimental setting, awareness of the research environment, and complexity and modalities of experiences. There were no differences in the prevalence or contents of experiences between those classified as unresponsive and responsive. Of all participants who could be interviewed, 49.0% reported subjective experiences, most frequently dreaming (98.0%). Incorporations of the experimental setting were also quite frequent (36.0%) while awareness of the environment was rare (4.1%). Participants receiving dexmedetomidine and S-ketamine reported subjective experiences most often and S-ketamine induced the most multimodal experiences. This study shows that unresponsiveness does not equal unconsciousness, and that participant’s responsiveness during sedation with equipotent dose is not associated with the likelihood of reporting subjective experiences. Subjective experiences are frequently reported after sedation and the subjective experiences may slightly differ between anesthetics administered in equipotent doses. Further studies should not consider responsiveness as an indicator of consciousness and should focus on how to distinguish unresponsive individuals who can experience external stimuli from those unresponsive individuals who cannot.